Imatinib inhibits migration of normal human epidermal melanocytes and suppress the phosphorylation of C-kit - Xia, Jian-Xin; Li, Fu-Qiu; Urabe, Kazunori; Wang, Jin-Feng; Furue, Masutaka (Bangladesh Journal of Pharmacology, 2012)
To investigate the inhibitory effect of imatinib on the migration of normal human epidermal melanocytes (NHEM), the growth and differentiation of NHEM were measured by MTT assay. Transwell Cell Migration Assay was performed to determine the migration of NHEM following imatinib treatment. The phosphorylation of c-kit in NHEM after imatinib treatment was measured by western blot assay. Imatinib at 0.1 ?M, 1.0 ?M and 5.0 ?M could inhibit the SCF (50 ng/mL) induced NHEM migration and suppress the phosphorylation of c-kit in NHEM. The result concluded that imatinib can inhibit SCF induced NHEM migration and suppress the c-kit phosphorylation in NHEM. This provide theoretical basis for the prevention of post-treatment recurrence of nevus spilus.